PROBLEMATIKA HAK UNTUK DILUPAKAN DALAM UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK (PERSPEKTIF HAM DAN TRANSPARANSI PUBLIK) - Hartanto, Hartanto; Noferani, Rudad; Ababil, Muhamad Afghan (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
The rapid use of the internet in Indonesia as part of the world community has created dynamics and problems, in the field of information law and electronic transactions as well as human rights, and also related to one's privacy. The government holds the power to regulate the new world, namely cyberspace for internet users in Indonesia. The right to be forgotten is a person's right that must be protected by the state. In this case, through Law No. 19 of 2019 concerning Electronic Transactions and Information. The right to be forgotten in relation to those who are reported on or whose data is stored in public institutions in relation to perpetrators of criminal acts, victims of criminal acts, or related to news of criminal acts can be both positive and negative if it is misused. Someone who is published in the public space that he was once a victim or perpetrator of a crime certainly has the right to be forgotten so that he can improve himself without the shadow of a dark past. On the other hand, public transparency still requires information to be accessed for certain news. For example, criminal acts of corruption. Bearing in mind human rights and public transparency regarding the classification of who is allowed and who is not allowed to use this right, it must be strictly regulated, for example, criminal acts of corruption.